Environmental control of CO2 assimilation rates and stomatal conductance in five oak species growing under field conditions in Greece (Ann. For. Sci., 1996)
The present study compared CO2 assimilation rate and stomatal conductance of five oak species from the beginning of May through November 1993 under similar natural conditions. Gas exchange, leaf characteristics and water status were measured on 30-year-old Quercus ilex, Q macrolepis, Q pedunculiflora, Q pubescens and Q trojana growing in experimental plots in northern Greece. The seasonal pattern of assimilation rates was similar for all study species but differences occurred between the species. After initial leaf expansion, all species rapidly developed high photosynthetic rates. In addition, assimilation rates were high in all species in May and November after rain events. No significant differences in stomatal conductance were observed among species during the growing season. The relationships between assimilation rate and stomatal conductance displayed variation in the slopes among species and months.